PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING TOURNAMENT TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SIWA KELAS VIII SMPN 3 BATANG ANAI - Irmayenti, Irmayenti; Zulfaneti, Zulfaneti; Cesaria, Anna (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ The background of this research is about studentâs understanding of mathematical concept are low. It seen from the result of studentâs learning class VIII SMPN 3 Batang Anai Academic Year 2013/2014. The aim from this research is to know the studentâs uderstanding of mathematical concepts by implementing active learning strategies type Learning Tournament better than studentâs uderstanding of mathematical concepts with conventional learning class VIII SMP 3 Batang Anai. This research is experimental with random desaign on the subject. The instrument used this research is studentâs uderstanding of Â mathematical concept test. The type of test is essay with reliabilitas test is = 0.97. DataÂ analysis technique used is the one parties t-test. Based on the calculation results of data alnalisys that the class normally distributed sample with Â and . Hypothesis test results obtained Â then the hypothesis in this research is received. So Â the studentâs understanding of mathematical concepts by implemeting strategies active learning tournament is better than the studentâs understanding of Â mathematical concepts that studentâs with conventional learning in the class VIII SMPN 3 Batang Anai 2013/2014.